The rate and molecular spectrum of spontaneous mutations in Arabidopsis thaliana - Ossowski, Stephan; Schneeberger, Korbinian; Lucas-Lledó, José Ignacio; Warthmann, Norman; Clark, Richard M; Shaw, Ruth G; Weigel, Detlef; Lynch, Michael (Science (American Association for the Advancement of Science), 2010)
To take complete advantage of information on within-species polymorphism and divergence from close relatives, one needs to know the rate and the molecular spectrum of spontaneous mutations. To this end, we have searched for de novo spontaneous mutations in the complete nuclear genomes of five Arabidopsis thaliana mutation accumulation lines that had been maintained by single-seed descent for 30 generations. We identified and validated 99 base substitutions and 17 small and large insertions and deletions. Our results imply a spontaneous mutation rate of 7 x 10(-9) base substitutions per site per generation, the majority of which are G:C-->A:T transitions. We explain this very biased spectrum of base substitution mutations as a result of two main processes: deamination of methylated cytosines and ultraviolet light-induced mutagenesis.